Strategies for early detection of cardiotoxicities from anticancer therapy in adults: evolving imaging techniques and emerging serum biomarkers. (July 2015) - Akhter, Nausheen; Murtagh, Gillian; Yancy, Clyde
Significant advances have been made in detecting cancer therapeutics-related cardiac dysfunction with serum biomarkers, cardiovascular MRI, echocardiography and multi-modality approaches. Serum biomarkers, notably cardiac troponins and natriuretic peptides, have been evaluated for their prognostic ability in predicting left ventricular dysfunction. Imaging modalities, such as cardiovascular MRI and echocardiography, have been used for cardiac surveillance of patients with cancer undergoing chemotherapy. Developments in imaging, specifically myocardial deformation imaging, also known as strain, have been shown to be sensitive tools in detecting early changes in cardiac function. This review aims to synthesize the evidence that supports emerging serum biomarkers and complementary imaging modalities that continue to enhance the detection of cancer therapeutics-related cardiac dysfunction.